Solid State Perovskite Solar Modules by Vacuum-vapor Assisted Sequential Deposition on Nd:YVO4 Laser Patterned Rutile TiO2 Nanorods - Azhar, Fakharuddin; Palma, Alessandro L.; Giacomo, Francesco Di; Casaluci, Simone; Matteocci, Fabio; Wali, Qamar; Rauf, Muhammad; Carlo, Aldo Di; Brown, Thomas M.; Rajan, Jose (IOP Publishing Ltd, 2015)

(untitled)
The past few years have witnessed remarkable progress in solution-processed methylammonium lead halide (CH3NH3PbX3,X - halide) perovskite solar cells (PSCs) with reported photoconversion efﬁciency (η) exceeding 20% in laboratory-scale devices and reaching up to 13% in their large area perovskite solar modules (PSMs). These devices mostly employ mesoporous TiO2 nanoparticles (NPs) as an electron transport layer (ETL) which provides a scaffold on which the perovskite semiconductor can grow. However, limitations exist which are due to trap-limited electron transport and non-complete pore ﬁlling. Herein, we have employed TiO2 nanorods (NRs), a material offering a two-fold higher electronic mobility and higher poreﬁling compared to their particle analogues, as an ETL. A crucial issue in NRs’ patterning over substrates is resolved by using precise Nd:YVO4 laser ablation, and a champion device with η∼8.1% is reported via a simple and low cost vacuum-vapor assisted sequential processing (VVASP) of a CH3NH3PbI3 ﬁlm. Our experiments showed a successful demonstration of NRsbased PSMs via the V-VASP technique which can be applied to fabricate large area modules with a pin-hole free, smooth and dense perovskite layer which is required to build high efﬁciency devices.